Konvergensi Media Dan Perubahan Komunikasi Massa - Setiawan, Ali Arif (Universitas Surakarta, 2010)
Abstract The development of information technology triggers a phenomenon known as media convergence in which the pooling of information technology services that had been insulated by the characteristics of each form of media. It triggers the technical development of news presentation, format and public goals including the subject of several interested parties. In fact, convergence is likely to trigger a change in public behavior that once served as principals of journalism by using the same media facilities with professional journalistic media. The problem is some negative effects also occur in some public groups that are not ready to receive media convergence is so necessary supervision and regulation of related party. Keyword: konvergensi, perubahan media.